A National Survey of the Prevalence and Impact of Cytomegalovirus Infection Among Hospitalized Patients With Ulcerative Colitis. Issue 3 (March 2018) - Grossberg, Laurie B.; Ezaz, Ghideon; Grunwald, Douglas; Cohen, Jonah; Falchuk, Kenneth R.; Feuerstein, Joseph D.
Abstract : Goals: To estimate the effect of cytomegalovirus (CMV) in patients with ulcerative colitis (UC), and compare these outcomes to patients with CMV without UC. Background: The impact of CMV infection in UC is not well understood. Study: We analyzed records from the Nationwide Inpatient Sample (NIS) of patients with UC and CMV between 2006 and 2012. Differences in outcomes were determined between patients with UC and CMV and those with UC without CMV. Secondary analysis compared outcomes of patients with UC and CMV to patients with CMV alone. Results: Patients with UC and CMV (n=145) had longer length of stay (16.31 vs. 5.52 d, P <0.0001), higher total charges ($111, 835.50 vs. $39.895, P =0.001), and were less likely to be discharged home without services (50.0% vs. 81.83%, P <0.0001) compared with patients with UC without CMV (n=32, 290). On regression analysis, CMV was significantly associated with higher total charges ( P <0.01) and longer length of stay ( P <0.01), but not for increased need for colorectal surgery. When comparing patients with UC and CMV to patients with CMV alone (n=14, 960), patients with CMV alone had a higher Charlson Comorbidity Index and a trend toward higher in-hospital mortality. Conclusions: CMV infection in hospitalized patients with UC is associated with a longer length of stay, increased total charges, and fewer routine discharges, but not increased surgery or mortality. Patients with CMV alone had the worst outcomes of all groups suggesting that CMV in UC patients may not have the same negative impact as in other diseases. Abstract : Supplemental Digital Content is available in the text.